NU dan Musik Religi: Dialektika Agama dan Budaya - Riyadi, Abdul Kadir; Amrullah, Moh. Adib (Tebuireng: Journal of Islamic Studies and Society, 2022)
Music, in its development, follows social and cultural needs. In the Islamic world, music has long been discussed in terms of how Islamic law regulates the use of musical instruments or listening to songs. From the two opinions that allow and prohibit, Nahdlatul Ulama has long engaged in a dialectic of musical art with religious law through the provision of a platform for both containing and developing musical art. Through the approach of Sufism and historical evidence of the success of preaching through art, religious music, which is a manifestation of the transformation of musical art in the present, has become one of the effective media for spreading Islamic values among children and the general public.